The Mediating Role of Job Satisfaction Between Leadership and Organizational Performance and the Moderating Effect of Educational Context - Fahrettin Gılıç , Sedat Kanadlı , Yüksel Gündüz , Yusuf İnandı (Educational Process: International Journal)
Background/purpose. Leadership behaviors correlate with job satisfaction, which is supposed to have impact on overall organizational performance. This study aimed to establish a model to explain organizational performance by determining the relational effect size between transformational and transactional leadership, job satisfaction, and organizational performance, and to examine the moderating effect of educational context.